An update of the types of Heteroptera (Hemiptera) housed at the Museo de La Plata Entomological Collection (Argentina) - Montemayor, Sara Itzel; Dellapé, Pablo Matías (Zootaxa, 2013)
We present a list of the type material of Heteroptera deposited in the entomological collection of the Museo de La Plata (Buenos Aires, Argentina) in the last six years and or, not included in previous catalogs. This catalog includes 244 specimens belonging to 43 holotypes, one neotype, and 200 paratypes. The type material examined belongs to 50 species from 43 genera distributed in 16 families: Schizopteridae, Hydrometridae, Naucoridae, Thaumastocoridae, Miridae, Tingidae, Vianaididae, Reduviidae, Alydidae, Rhopalidae, Largidae , Berytidae, Blissidae, Lygaeidae, Oxycarenidae, and Rhyparochromidae.